2019
DOI: 10.26442/00403660.2019.03.000129
|View full text |Cite
|
Sign up to set email alerts
|

Possibilities of ultrasound research of the diaphragm

Abstract: The ultrasound method is a non-invasive and safe diagnostic method. Ultrasound examination (ultrasound) of the diaphragm allows you to conduct a direct study of its structure and function. Using stationary and portable ultrasound scanners, the study of the diaphragm can be carried out in specialized laboratories, in outpatient departments, in various departments of the clinic, including in intensive care units, in patients in different clinical conditions. Ultrasound of the diaphragm can be implemented on devi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 66 publications
1
5
0
Order By: Relevance
“…Te diaphragm morphological structure and function are often refected by measuring diaphragm thickness, its change rate, and excursion during inhalation and exhalation. Although the diaphragm changes rhythmically with breathing, the ultrasound evaluation of the diaphragm still has high accuracy and consistency [16,33,34]. Tis study also found high intrarater reliability (ICC varied from 0.906 to 0.964) which was in line with the other studies [35,36].…”
Section: Discussionsupporting
confidence: 80%
“…Te diaphragm morphological structure and function are often refected by measuring diaphragm thickness, its change rate, and excursion during inhalation and exhalation. Although the diaphragm changes rhythmically with breathing, the ultrasound evaluation of the diaphragm still has high accuracy and consistency [16,33,34]. Tis study also found high intrarater reliability (ICC varied from 0.906 to 0.964) which was in line with the other studies [35,36].…”
Section: Discussionsupporting
confidence: 80%
“…Ultrasonography is non-invasive and radiation-free and permits easy and accurate assessment of the diaphragm anatomy and function [27]. US equipment is ubiquitously present in ICU units, and diaphragm US can be conveniently performed at the bedside, without the need for additional efforts by patients [28].…”
Section: Discussionmentioning
confidence: 99%
“…Sonographic evaluation is an imaging modality that is gaining popularity in ICU for the evaluation of diaphragmatic function 18 . Ultrasonography is noninvasive and radiation-free, allowing easy and accurate assessment of diaphragm anatomy and function 19 .…”
Section: Discussionmentioning
confidence: 99%